ISLAMIC MODERN BOARDING SCHOOL IN REVIEW PHILOSOPHY OF ISLAMIC EDUCATION - Usiono, Usiono (Proceeding International Seminar of Islamic Studies, 2024)
The rise of Europe with the spirit of modernism has influenced all corners of the world, including Islamic education in Indonesia, namely pesantren. The emergence of modern pesantren is seen as an answer to the challenges of the times, so that Muslims no longer rely on the traditional education system. This study aims to review how the concept of modern pesantren is viewed in the philosophy of Islamic education. The research method used is library research, which is a study that examines books and manuscripts sourced from literature. The results of this study show that there are differences in Islamic countries in anticipating the spirit of European modernism, one of which is the Ottoman Turkish Daulah which maintains the purity of madrasa education, and establishes a new school called the Rusydiyyyah school which is devoted to studying modern sciences from Europe.